Pembuatan CMC (Carboximethyl Cellulose) dari Sellulosa Bakterial (Nata de Coco) - Murna Muzaifa (Fakultas Pertanian, Universitas Syiah Kuala, 2006)
Production of CMC (Carboximethyl Cellulose) from Bacterial Cellulose (Nata de Coco)ABSTRACT. Bacterial cellulose (nata de coco) has been used as source of cellulose in CMC (Carboximethyl Cellulose) production. This research has been conducted to study the optimum formulation of CMC production from nata de coco. Factorial Randomized Completely Design was employed with two factors that were concentration of NaOH (10%, 15%, and 20%) and amount of NaMCA (10g, 3g and 16g). The result showed that concentration of NaOH and amount NaMCA significantly affected moisture content, degree of eterification (DE), yield, and viscosity. The combination of NaMCA at 16 g and NaOH at 15% produced the best treatment with characteristics: 10,12% of moisture content, 0,9 of degree of eterifiication, 40,40% of yield and 25,41 of viscosity.